Ризики культивування субтропічних плодових культур у лісостеповій зоні України - Красовський, Володимир; Черняк, Таїсія; Krasovsky, Volodymyr; Chernyak, Taisiya (Східноєвропейський національний університет імені Лесі Українки, 2016)
На прикладі Полтавської обл., природно-кліматичні умови якої є типовими для фізико-географічної зони Лісостепу України, показано, що в окремі роки в зимовий період сукупна дія низьких від’ємних температур повітря та вітру може бути критичною з огляду на морозостійкість інтродукованих видів Asimina triloba (L.) Dunal, Punica granatum L., Zizyphus jujuba Mill., Ficus carica L., Amygdalus communis L., Diospyros virginiana L. Recent years spreading of some subtropical fruit crops on the plots caused with introduction activity of botanical garden, plays an important role for increasing of fruit species in the forest-steppe zone of Ukraine. They are Asimina triloba (L.) Dunal, belonging to the family Annonaceae DC., Punica granatum L., belonging to the family Lythraceae J. St-Hil., Zizyphus jujuba Mill., belonging to the family Rhamnaceae R. Br., Ficus carica (L.) belonging to the family mulberry Moraceae Link, Amygdalus communis L., belonging to the family Rosaceae Juss., Diospyros virginiana L., belonging to the family Ebenaceae Guer. It was taken Poltava region, which native climatic conditions are typological for physical and geographical zone of Ukrainian forest-steppe and observed that some years the effect of air low temperature during winter period can be dangerous.
Risks of Cultivation of Subtropical Fruit Crops in the Foreststeppe Zone of Ukraine.
Keywords: Лісостеп України; сукупна дія морозу та вітру; субтропічні види; інтродукція; the forest-steppe zone of Ukraine; the combined effect of frost and wind; subtropical species; іntroduction